Evaluasi aktivitas fraksi hexan rimpang kunyit (Curcuma longa) dalam persembuhan luka pada mencit - W. Winarsih .; I. Wientarsih .; E. Handharyani .; R. M. Almira . (Hemera Zoa, 2010)
The aim of this research was to evaluate the affectiveness of hexane fraction of ethanol turmeric extract on the wound helaing process of mice. The extraction process was based on maseration method. Fourtyfive male albino mice aged 2-2,5 month were divided into 3 groups, all groups were received incision 1 cm on their back skin; group I was positive control (treated with commercial oitment which contained neomycin sulfat 5%); group II was negative control (without treatment); group III was treated by hexane turmeric fraction ointment. The commercial ointmnetand hexane turmeric fraction ointmnet were given topically twice a day. Three mice from each gropus were euthanized at 2nd, 4th, 7th, 14th, and 21st days post incisition (pi) for gross pathology abservation and microscopic lesions of the injured skin. Phytochemical analysis resulted that the hexane turmeric fraction contain alkoloid, kuinon and saponin. Gross examination revealed that the hexane turmeric fraction and positive control gropus showed better result an woud healing process compared to the negative control. Histophatology of the hexane fraction treated mice showed few neutrophil with increase in collagenation and neovascularization compared to the negative control. Based on the macroscopic and microscopic observation, the hexane turmeric fraction has properties which promotes wound healing.